An Arrhenius equation-based model to predict the residual stress relief of post weld heat treatment of Ti-6Al-4V plate. (April 2018) - Yan, Guangxu; Crivoi, Alexandru; Sun, Yajuan; Maharjan, Niroj; Song, Xu; Li, Feng; Tan, Ming Jen
Abstract: Creep models are generally utilized for predicting the residual stress relief during post weld heat treatment (PWHT). However, a comprehensive model considering the temperature effect is still lacking. In the present work, a new temperature dependent Arrhenius equation-based model has been developed to predict the residual stress relief of PWHT of Ti-6Al-4V. The model was validated by the surface residual stress measurement of the Ti-6Al-4V plate before and after PWHT using X-ray Diffraction (XRD). The comparative study of modelling results and measurements indicates that the temperature dependent Arrhenius equation-based model developed in this work is accurate and effective for predicting the residual stress relief of PWHT of Ti-6Al-4V. Besides, the creep induced strain increment takes the dominant role in residual stress relief during the PWHT process of Ti-6Al-4V.